ANALISIS MISKONSEPSI SISWA PADA MATERI POKOK LINGKARAN DITINJAU DARI KESIAPAN BELAJAR DAN GAYA BERPIKIR SISWA KELAS XI IPA SMA N 3 SURAKARTA TAHUN AJARAN 2013/2014 - Wardani, Endang Purwati; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purposes of this research were: (1) knowing the characteristics of the misconception, and (2) knowing the causes of the misconception of the XI grade students in the academic year of 2013/2014 inÂ  equation of circle and equation of tangent line of a circle viewed from the studentâs readiness and style of learning. Qualitative research was applied in this research. The subject of the research are students of the eleven grade of SMA Negeri 3 Surakarta. The source of data was taken from informants (students), documentation (questionnaire), and test. Data collection was taken by using interview, diagnostic test, and questionnaire. Data validity used the source of triangulation. Data analysis used Miles and Hubermanâs concept that are data collection, data reduction, presenting the data, and drawing the conclusion. The result of the research showed as follows: (1) students who are ready to learn and have the synthetic thinking style in understanding the locus of a point on the circle and determining the equation of tangent line ofÂ  a circle,Â  experience a misconception of theoretical concept. Meanwhile, in determining the circle equation, the students who are ready to learn with synthetic thinking style, donât have any misconception.Â  (2) Students who are ready to study and have analytic thinking style in determining the equation of circle (determining the center point and the radius) experience a misconception in co relational concept. In understanding the locus of a point on the circle and determining the equation of tangent of line, students who are ready to study with analytical thinking style, experience a misconception in theoretical concept. (3) Students who are not ready to learn with synthetic thinking style experience a misconception in determining the equation of a circle (determining the center point and the radius), the misconception is in co relational and theoretical concept. In determining the equation of tangent line of a circle, students who are not ready with synthetic thinking style experience misconception of theoretical concept. While in understanding the locus of a point on the circle, generallyÂ Â  students who not ready to learn with synthetic thinking style do not experience misconception. (4) Students who are not ready to learn with analytical thinking style experience misconception in determining the equation of circle (determining the center point and radius), namely the misconception of co relational and theoretical concepts. In determining the locus of a point on the circle, students who are not ready to learn with the analytical thinking style experience misconception of theoretical concept. (5) In general the cause of misconception for the students is the difficulty of the students to classify the form of the equation of the circle and the equation of tangent line of a circle.Keywords: misconception, readiness to learn, thinking style